The inhibitory effect of vitamin E on cigarette smoke-induced oxidative damage to the rat urothelium: Can it prevent transitional cell carcinoma? - YÜKSEL, MERAL (KARGER, 2007)
Introduction: We aimed to detect reactive oxygen species ( ROS) and assess subsequent carcinogenesis in terms of cellular proliferation in the bladder and kidney epithelial tissues of rats exposed to cigarette smoke ( CS), and to investigate the changes following vitamin E treatment. Materials and Methods: Twenty- four male Sprague- Dawley rats were divided into 3 groups: group 1 was kept intact; group 2 was subjected to CS exposure for 8 weeks, and group 3 received intraperitoneal vitamin E injections ( 200 mg/ kg/ week) for 8 weeks in addition to CS exposure. Histological examination and Ki67 antigen expression measurements were made from bladder and renal pelvic tissue sections. Luminol- amplified chemiluminescence was used to measure ROS levels. All results were compared using a one- way ANOVA test. Results: In CS- exposed rats, light microscopy of renal and bladder tissues revealed nonspecific epithelial changes; however, Ki67 expression was significantly increased in bladder tissues compared to other groups ( 17.5 +/- 4.7, 35 +/- 2.9 and 18.7 +/- 5.1% in groups 1, 2 and 3, respectively, p < 0.05). Chemiluminescence levels in bladder and renal tissues were also significantly higher in the CS-exposed animals ( 78.1 +/- 11.4, 148 +/- 13.3, 97.8 +/- 6.1 rlu/ mg for the bladder, and 99.8 +/- 12.2, 176.1 +/- 27.9, 67.1 +/- 9 rlu/ mg, for renal pelvic tissues, respectively, p < 0.05). Conclusions: Vitamin E can alleviate CS- induced oxidative damage in rat bladder and kidney epithelium suggesting a potential role for vitamin E in the prevention of CS- mediated carcinogenesis. Copyright (c) 2007 S. Karger AG, Basel.
Keywords: transitional cell carcinoma; cigarette smoke; oxidative damage, prevention; vitamin E; BLADDER-CANCER; DNA-ADDUCTS; LIPID-PEROXIDATION; BETA-CAROTENE; PLASMA; DIETARY; TISSUE; COHORT; BLOOD; LUNG